Perspective on solid‐electrolyte interphase regulation for lithium metal batteries. (29th December 2020) - Wu, Mingguang; Li, Yong; Liu, Xinhua; Yang, Shichun; Ma, Jianmin; Dou, Shixue
Abstract: The solid‐electrolyte interphase (SEI) generated between the electrode and the electrolyte strongly influences the performance of batteries. As the most attractive next‐generation energy storage system with ultrahigh energy density, the development of lithium metal batteries (LMBs) has been greatly plagued by the uncontrollable lithium (Li) dendrite and serious electrolyte decomposition resulting from the self‐derived unstable SEI with poor properties. In this perspective, the recent progress of regulating the nature and composition of the SEI to stabilize the Li metal in LMBs is summarized, followed by a discussion of the formation mechanism and the property of the SEI. The strategies for constructing a stable SEI are summarized, for example, design of a compatible electrolyte with the anode, adding self‐sacrificing additives or solvation control additives, and the regulation of nonfaradaic electric adsorption and desorption progress. Finally, the guideline for the rational design of the SEI is proposed. Graphical Abstract: In this perspective, the properties of ideal solid electrolyte interphase are discussed, and the corresponding strategies for solid electrolyte interphase regulation in lithium metal batteries are also proposed.